Judy Moody saves the world! - McDonald, Megan; Reynolds, Peter H. (Peter Hamilton), 1961- (Somerville : Candlewick Press, 2002)
When Judy Moody gets serious about protecting the environment, her little brother Stink thinks she is overdoing it, but she manages to inspire her third grade class to undertake an award-winning, environment-saving project.
K
b
b
Keywords: Moody, Judy (Fictitious character) -- Juvenile fiction; Mood (Psychology) -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Recycling (Waste, etc.) -- Juvenile fiction; Children's stories